INTERLANGUAGE PROCESS - Novasyari, Ressy (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2020)
Abstract This article describes about the definition of Interlanguage process andinterlanguage process. An interlanguage is an emerging linguistic systemthat has been developed by a learner of a second language (or L2) whohas not become fully proficient yet but is only approximating the targetlanguage: preserving some features of their first language (or L1) inspeaking or writing the target language and creating innovations.Interlanguage is the type of language produced by second- andforeign- language learners who are in the process of learning alanguage. Interlanguage refers to the separateness of a secondlanguage learner’s system, a system that has a structurallyintermediate status between the native and target language.Keywords: Definition of Interlanguage process and Interlanguage proces